THE IMPORTANCE OF THE INTERNAL AUDIT SYSTEM TODAY - Khasanova Nasiba Tolliboy qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
One of the key areas of internal audit activity is the identification and analysis of potential external and internal risks in the development and implementation of new projects, as well as the preparation of recommendations aimed at reducing the level of risk or minimizing possible losses. Internal auditors also monitor the expenditure of financial resources for various projects or programs (for example, a capital construction project or a product launch program), and analyze the company’s financial and management reporting in terms of their reliability and timeliness. In addition, auditors evaluate signed contracts and the fulfillment of contractual obligations by the parties, and they are involved in assessing control systems within existing and newly implemented information systems.